Effects of weaning time, light regime, and stocking density on growth, condition, survival, and cannibalism rates in northern pike (Esox lucius L.) larvae and early juveniles under intensive culture - Imentai, Aiman; Bondarenko, Volodymyr; Pěnka, Tomáš; Policar, Tomáš (Frontiers in Marine Science, 2024)
In this study, three separate experiments were conducted to optimize the intensive larviculture of pike (Esox lucius L.) under different weaning times, light regimes, and stocking densities. In the first experiment, larvae were fed sequential combinations of live feed (LF), co-feeding with dry starter (DS), and only DS feed for 18 days as follows: 9 days LF followed by 3 days co-feeding and 5 days DS (group A); 6 days LF followed by 3 days co-feeding and 9 days DS (group B); 3 days LF followed by 3 days co-feeding and 12 days DS (group C); and DS alone for 18 days (group D). Fish fed LF had significantly higher growth rates than those fed a dry diet (P<0.05). Extending the feeding period on LF resulted in a significantly higher growth rate (24.6%.d -1 ), variability (13.5%), and heterogeneity (299.5%.d -1 ) than fish fed a DS. In the second experiment, the effect of the light regime was assessed at eight different levels (